Power after Power: Arendt on Power Accumulation in “Leviathan” - Kravanja, Aljoša (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Hannah Arendt claims that Thomas Hobbes argued for power accumulation, offering what she describes as the “blueprint” for 19th-century imperialism. Her reading is often criticized for being biased and hostile towards Hobbes. Yet the paper contends that her interpretation has one advantage. In Leviathan, Hobbes fails to deduce the need to acquire “power after power” from his theory of desire. Arendt bridges this gap by proposing that Hobbes tied power accumulation to capital acquisition: when power is seen as supporting economic growth rather than our natural desires and social ambitions, its accumulation can become limitless. On the other hand, the paper argues that Arendt overlooks the upper boundary of Hobbesian power accumulation. As shown by his discussions on popularity and colonial expansion, Hobbes thinks that both private subjects and states ought not to accumulate power indefinitely.
Keywords: Arendt; Hobbes; “Leviathan”; power; imperialism